N-tert-Butyl O-2-isopropyl-5-methylcyclohexyl phenylphosphonamidate - Liu, Li-Juan (International Union of Crystallography, 2011)
In the title compound, C(20)H(34)NO(2)P, the P atom has an irregular tetrahedral environment and exhibits S (p) chirality. In the crystal, weak intermolecular N—H⋯O and C—H⋯O hydrogen bonds link the molecules into chains extending in [010].